Aplicativo sobre processo de enfermagem em uma unidade de terapia intensiva neonatal - Araujo, Jhonathan Lucas (2018)
Introduction: The nursing process is the recommended instrument for the operationalization of nursing care. In a Neonatal Intensive Care Unit (NICU), it is still performed in a fragmented way and does not use a taxonomy to substantiate it. Objective: To develop an application to perform the nursing process in the care of the newborn. Methodology: This is a qualitative, two-step study. In the first, the participative methodology of action research, provided a survey of the obstacles to the accomplishment of the nursing process. To solve the problems, four seminars were held to elaborate and validate instruments for acessment, diagnostic and nursing interventions considering the theoretical reference of the Basic Human Needs (NHB) of Wanda Horta and the taxonomy of the International Classification for Nursing Practice. The seminars took place between the months of January and March of 2017, the talks were recorded and transcribed for later content analysis. In the second stage, an application was developed and validated to operationalize the execution and registration of the nursing process, considering the norms for software engineering. The application was elaborated from March 2017 to February 2018. The evaluation and validation was performed in February 2018 by a technical team and eleven nurses from the NICU of a university hospital in the southeast of Brazil. Results: Instruments for the nursing process were elaborated and validated, which were the basis for the elaboration of the application, also validated by the nurses. Products: An instrument for the acessment and nursing diagnosis and another for nursing interventions were developed. The acessment instrument was elaborated in three pages, containing each NHB relative to the first stage of the nursing process for the neonatal patient. Psychobiological NHB followed the psychosocial ones. The psychospiritual NHB was not contemplated. The content of the acessment includes the evaluation of clinical indicators, devices and other relevant information. The nursing diagnoses were inserted in the same instrument, related to the acessment and the clinical indicators. The instrument for nursing interventions proposes 160 separate actions for each of the 36 proposed diagnoses, subsidizing the nurses' planning. The "CuidarTech Neo" mobile application was also developed to support the execution and registration of the nursing process. This, crosses data from the acessment with nursing diagnoses, assisting the nurse in the clinical judgment and diagnostic decision. In addition, it provides storage of collected data for later reference or change. It also associates with other interfaces and working devices, enabling the printing of historical data, diagnosis and nursing interventions, or storage in electronic medical records. Conclusion: The nursing process is a daily tool of nursing care. Technologies that make it more effective and efficient are necessary, aimed at improving the quality and assertiveness of nursing care. An application that operationalizes the nursing process may be able to make nursing care safer, faster and more scientific.